Physics, asked by dezzire, 1 year ago

(c) Iad=3Ief
(d)Iac=Ief


solve properly....
Don't spam... Otherwise answer will be reported.

Attachments:

Answers

Answered by TheEmpress
44
BONJOUR FRIEND ♥
HERE'S THE ANSWER ✌
♦♦♦♦♦♦♦♦♦♦♦♦♦♦♦♦♦♦

⤴⤴⤴⤴⤴
HOPE YOU FIND IT HELPFUL ☺☺☺
Attachments:
Answered by brainlystargirl
8
Heya sis ^_^

Answer ___________

Let the I be the MI of square lamina then by using the II axes theorem :-

Iac + Ibd = I
Iac = 1/2

Again by II axis theorem :-

Ief + Igh = I
Ief = 1/2

Thus....

Iac = Ief ....

Thank you
Similar questions